THE APPLICATION OF TRANSLATION TECHNIQUES IN TRANSLATING - Khairunnisa Br. Batubara; Rizki Ananda Sinurat; Ilyas Fadhil Sebayang; Venia Christina Bukit (TRANSFORM : Journal of English Language Teaching and Learning, 2022)
According to Career Explorer, the translator profession is a job that is responsible for changing the written word from one language to another. This study discusses the translation techniques used for translating. The data of this study is descriptive qualitative based on types and sentences that use translation techniques based on Molina and Albir's theory taken from the translation text. In gathering the data, the researchers use the interview method. Based on the data analysis, use 8 techniques found in the data. The results show (1) borrowing occurs 10 times and represents 1.8%, (2) literal occurs 5 times and represents 3.6%, (3) calque occurs 3 times and represents 6%, (4) equivalent occurs 1 time and represents 18%, (5) Description occurs 1 time and represents 19%, (6) application occurs 2 times and represents 9%, (7) modulation occurs 2 times and represents 9% (8) compensation occurs 1 time and represents 18%.